THE ROLE OF LOCAL WISDOM VALUES IN THE IMPLEMENTATION OF THE DEVELOPMENT OF NAGARI KAMANG MUDIAK, AGAM DISTRICT, WEST SUMATERA - Widesma, Annisa Vira; Adnan, M. Fachri (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to find out the Role of Local Wisdom Values in the application of the Development of Nagari Kamang Mudiak, Agam Regency. The role of the community and institutions in nagari development is not only limited to benefit owners, but also actively involved in development programs. The condition of local customary institutions will influence their role in the development of the nagari. Data collection techniques in the form of field research by means of interviews, Focus Group Discussion (FGD), and study documentation with primary and secondary sources. The research findings show that the result of government interference with the Nagari government from time to time indirectly makes the role of indigenous local institutions diminish in the development of the Nagari. The role of indigenous local institutions in the development of nagari still exists in every step of rural development, where the dominance of roles is in fact the planning and coordination stage.